Pengaruh Kepemimpinan dan Kompensasi terhadap Kinerja Karyawan PT Pertamina (Persero) Unit Pengolahan V Balikpapan melalui Motivasi - Makmur Makmur; E. Retno Maninggarjati; Ahmad Sirri (Jurnal EKSIS, 2022)
One of the heavy assiagment carried out by PT Pertamina (Persero) is fulfilling oil and gas needs. Then the implementation of the system in the organization must be done well because of this purpose research (1) to find out the leadership will have a positive and significant effect to employee motivation (2) to find out compensation will have a positive and significant effect to motivation (3) to find out the motivation positive and significant to employee performance (4) to find out leadership will have a positive and significant effect to employee performance (5) to find out compensation will have a positive and significant effect to employee performance (6) to find out leadership and compensation will have a positive and significant effect to motivation. The method of collecting data through questionnaires distributed to employees of PT Pertamina (Persero) Refinery Unit V samples taken as many as 80 respondents with the Probability Sampling Method. The analysis method used in this research is path analysis. From the results of the tests showed (1) leadership has a positive and significant effect to motivation (2) compensation has a positive and significant effect to motivation (3) motivation has a positive and significant effect to employee performance (4) leadership has a positive and significant effect to employee performance (5 ) compensation has a positive but not significant effect to employee performance (6) leadership and compensation have a positive and significant effect to employee performance through motivation.